Grist Mill Road [compact disc, unabridged] : a novel - Yates, Christopher J. (Macmillan Audio, 2017)
The year is 1982; the setting, an Edenic hamlet some ninety miles north of New York City. There, among the craggy rock cliffs and glacial ponds of timeworn mountains, three friends, Patrick, Matthew, and Hannah, are bound together by a terrible and seemingly senseless crime. Twenty-six years later, in New York City, living lives their younger selves never could have predicted, the three meet again, with even more devastating results.